Synthesis and Characterization of Sodium Aluminate from Aluminum and Sodium Hydroxide - Dinalia, Dinalia; Syamsi Aini; Jon Efendi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
The synthesis of sodium aluminate from aluminum and sodium hydroxide was successfully conducted to optimize its potential as a precursor for zeolite production. Aluminum was reacted with NaOH solution under continuous stirring for five hours, with variations in pH and Al-to-NaOH molar ratio to determine optimal synthesis conditions. The highest aluminum conversion (94.33%) was achieved at pH 13.6 and an Al-to-NaOH molar ratio of 1:4. Fourier-transform infrared (FTIR) spectroscopy confirmed the formation of tetrahedral [AlO₄]⁻ units through characteristic aluminate vibrational bands at 624 and 727 cm⁻¹. X-ray diffraction (XRD) analysis revealed sharp reflections at 2θ ≈ 34.8°, corresponding to crystalline NaAlO₂ (JCPDS No. 33-1200), indicating high crystallinity and phase purity. Scanning electron microscopy coupled with energy-dispersive X-ray (SEM–EDX) analysis showed irregular plate-like crystalline particles with a near-stoichiometric Na:Al ratio (~1:1), confirming compositional homogeneity. Overall, optimized alkalinity and stoichiometry were found to be critical for producing highly crystalline and compositionally pure sodium aluminate, suggesting its suitability as a high-quality, environmentally friendly precursor for zeolite synthesis.